Evaluating Anti-Corruption Education Implementation in Village Governance - A Case Study of PKM in Cipatujah District, Tasikmalaya Regency - Sidiq, Fahmi; Laksito, Grida Saktian; Azahra, Astrid Sulistya (International Journal of Research in Community Services, 2024)
Community Service (PKM) is an effort to increase understanding and quality of the role of village heads and village officials incarrying out government duties at the village level. PKM activities carried out in Cipatujah District, Tasikmalaya Regency, focuson materials such as good governance, anti-corruption education, and the role of village heads as government administrators. Theevaluation results showed a significant increase in participants' understanding of the materials. The instructions provided also helpparticipants understand their roles and responsibilities as effective village leaders. These positive results indicate that PKMactivities have made a positive contribution in strengthening the role of village heads and village officials in village development.It is hoped that the understanding and enthusiasm gained from this activity will continue in daily practice, creating a village that ismore advanced, empowered and has integrity.